2004
DOI: 10.1086/424512
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Chloroquine plus Sulfadoxine-Pyrimethamine versus Artesunate plus Mefloquine versus Artemether-Lumefantrine in the Treatment of Uncomplicated Falciparum Malaria in the Lao People's Democratic Republic

Abstract: Oral artesunate plus mefloquine and artemether-lumefantrine are highly effective for the treatment of uncomplicated falciparum malaria in Laos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 29 publications
6
72
0
1
Order By: Relevance
“…These predicted day 7 capillary plasma concentrations were approximately equivalent to the median venous plasma concentrations of 310 ng/ml (range, 94 to 1,364 ng/ml) determined by using the previously characterized relationship between capillary and venous concentrations (49). This is considerably lower than the corresponding values previously reported in nonpregnant adults and pediatric patients with multiresistant malaria in Thailand, Cambodia, and the Lao People's Democratic Republic (10,29,42,47). Price et al (42) reported a median day 7 venous plasma lumefantrine concentration of 528 ng/ml (range, 49 to 5,175 ng/ml) in Karen patients (n ϭ 201) receiving the same standard treatment of artemether-lumefantrine.…”
Section: Discussionsupporting
confidence: 48%
“…These predicted day 7 capillary plasma concentrations were approximately equivalent to the median venous plasma concentrations of 310 ng/ml (range, 94 to 1,364 ng/ml) determined by using the previously characterized relationship between capillary and venous concentrations (49). This is considerably lower than the corresponding values previously reported in nonpregnant adults and pediatric patients with multiresistant malaria in Thailand, Cambodia, and the Lao People's Democratic Republic (10,29,42,47). Price et al (42) reported a median day 7 venous plasma lumefantrine concentration of 528 ng/ml (range, 49 to 5,175 ng/ml) in Karen patients (n ϭ 201) receiving the same standard treatment of artemether-lumefantrine.…”
Section: Discussionsupporting
confidence: 48%
“…These results were in accordance with those of previous randomized studies reporting Day-42 cure-rate data with A-L in adolescents and adults from areas of multi-drug resistance, and applying a similarly conservative approach for analysis. 29,30 In conclusion, over a 6-week observation period, A-L administered twice daily for three consecutive days was well tolerated and highly efficacious for the treatment of acute uncomplicated P. falciparum malaria. Neither ABR latencies nor pure-tone thresholds showed clinical or statistical evidence of an effect of A-L on auditory functioning, confirming previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…By use of intention-to-treat analysis, the 42-day cure rates, adjusted for re-infections, were 100, 97 and 93% for the groups receiving AS-MQ, AL, and CQ-SP, respectively. This study demonstrates that oral AS-MQ and AL were highly effective for the treatment of uncomplicated falciparum malaria at the time (Mayxay et al, 2004). Monitoring of therapeutic efficacy and tolerability of AL versus AS-MQ in Senegal showed that the cure rate was 98.5% in the AS-MQ group versus 98.2% in the AL group at day 42 (p = 1).…”
Section: -Day In Vivo Protocol To Test Acts Efficacymentioning
confidence: 75%
“…The 28-day follow-up protocol (Chanda et al, 2006;Denis et al, 2002;Marquino et al, 2003) or 42-day follow-up protocol (Leang et al, 2015;Mårtensson et al, 2005;Mayxay et al, 2004;Valecha et al, 2010;Yeka et al, 2008) were usually used. Few studies used 63-day follow-up protocols for efficacy monitoring of ACTs containing a long half-life partner drug (Sodiomon et al, 2016;Valecha et al, 2010).…”
Section: In Vivo Act Efficacy Evaluationmentioning
confidence: 99%
See 1 more Smart Citation